1993
DOI: 10.1093/ije/22.4.674
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a Cohort of Pesticide Applicators in an Urban Setting

Abstract: The mortality of a cohort of 168 pesticide applicators employed in the disinfestation service of the city of Rome for an average of 20 years is examined. Exposure data were abstracted from work records, and causes of death for the 42 workers who had died, were obtained from death certificates. Standardized mortality ratios (SMR) for specific causes of death were computed on the basis of provincial mortality rates. An excess in mortality from cancer of the liver and bile ducts with four cases observed and 0.7 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Up to now, there is still not a clear profile of HCC pathogenesis factors, and the factors' interactions are also poorly understood. Some early studies showed rodents exposed to DDT and DDE can develop liver tumors (Kitagawa et al, 1984;Williams and Numoto, 1984); but the few epidemiological studies on DDT exposure and its correlation with mortality from liver cancer (Figatalamanca et al, 1993;Cocco et al, 1997Cocco et al, , 2000Cocco et al, , 2005 showed inconsistent results. The conflict may be due to the instability of exposure assessment only by survey but not using exposure biomarkers.…”
Section: Association Of Ocp Exposure and Hccmentioning
confidence: 99%
“…Up to now, there is still not a clear profile of HCC pathogenesis factors, and the factors' interactions are also poorly understood. Some early studies showed rodents exposed to DDT and DDE can develop liver tumors (Kitagawa et al, 1984;Williams and Numoto, 1984); but the few epidemiological studies on DDT exposure and its correlation with mortality from liver cancer (Figatalamanca et al, 1993;Cocco et al, 1997Cocco et al, , 2000Cocco et al, , 2005 showed inconsistent results. The conflict may be due to the instability of exposure assessment only by survey but not using exposure biomarkers.…”
Section: Association Of Ocp Exposure and Hccmentioning
confidence: 99%
“…Yet, lacking schistosomiasis-related information as well as employing unconditional logistic regression method for matched case-control data, their conclusion was possibly undermined by the biased estimates away from the null. Although the biological plausibility of carbamates and organophosphate pesticides are reported in animal models [47], the causal inference of human HCC as the consequences of insecticide or pesticide exposure are far from conclusive due to some methodological difficulties in observational studies [27,48]. By comparison, industrial workers have higher risk of HCC with administrative workers as reference group.…”
Section: Discussionmentioning
confidence: 99%
“…69 There were no NHL deaths (0.3 expected) reported in a Dutch cohort of licensed herbicide applicators, 54 while one NHL death (0.1 expected) was observed in a cohort of pesticide applicators employed in the disinfestations service of the city of Rome. 79 Findings from studies that evaluated risk of NHL among other occupational groups, including soil and forestry workers, mill workers, and lumberjacks, have varied. Individual pesticide exposure was not measured in these studies; rather, job title or industrial category was used as a surrogate for possible pesticide exposure.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%